Immunostimulated Arginase II Expression in Intestinal Epithelial Cells Reduces Nitric Oxide Production and Apoptosis - Talavera, Maria M.; Nuthakki, Sushma; Cui, Hongmei; Jin, Yi; Liu, Yusen; Nelin, Leif D. (Frontiers in Cell and Developmental Biology, 2017)
Increased production of nitric oxide (NO) and subsequent local cytotoxicity to mucosal epithelial cells has been proposed as a putative mechanism involved in the development of necrotizing enterocolitis (NEC). Intestinal epithelial cells (IECs) metabolize L-arginine to either nitric oxide (NO) by NO synthase (NOS) or to L-ornithine and urea by arginase. L-ornithine is the first step in polyamine synthesis important for cell proliferation, while NO production can lead to apoptosis. We hypothesized that in IECs immunostimulation increases both NOS and arginase expression, and that arginase activity mitigates NO production and apoptosis. Rat intestinal epithelial cells (rIEC-6) were immunostimulated by either incubation with lipopolysaccharide (LPS) alone for 24 hours or by incubation with conditioned media (CM) for 24 hours. CM was obtained from RAW 264.7 cells (a macrophage cell line) treated with LPS (E.coli 0127:B8; 1μg/ml) for 4 hours. The rIEC-6 stimulated with LPS or with CM had significantly higher levels of inducible NOS (iNOS) protein, NO production, and arginase II protein than did the control cells. Direct LPS stimulation of rIEC-6 produced a less robust increase in iNOS expression and NO (represented as nitrite percent of control) than did CM stimulation. Inhibition of arginase using Nω hydroxyl-L-arginine (NOHA) further increased stimulated NO production in rIEC-6. Viable cell numbers were significantly lower in CM stimulated cells after 24 hours than in controls, and inhibition of arginase activity with NOHA resulted in a further significant decrease in viable cell numbers. We conclude that inflammation-induced arginase expression of rIEC-6 cells tempers cytokine-induced iNOS-derived NO production and apoptosis.